A re‐examination of the US insurance market's capacity to pay catastrophe losses. Issue 4 (11th December 2022) - Dionne, Georges; Desjardins, Denise
Abstract: Cummins, Doherty, and Lo (2002) present a theoretical and empirical analysis of the capacity of the property liability insurance industry in the US to finance catastrophic losses. In their theoretical analysis, they show that a sufficient condition for capacity maximization is for all insurers to hold a net of reinsurance underwriting portfolio that is perfectly correlated with aggregate industry losses. Estimating capacity from insurers' financial statement data, they find that the US insurance industry could adequately fund a $100 billion event in 1997. As a matter of comparison, Hurricane Katrina in 2005 cost the insurance industry $40 to $65 billion (2005 dollars). Our main objective is to update the study of Cummins et al. (2002) with new data available up to the end of 2020. We verify how the insurance market's capacity has evolved over recent years. We show that the US insurance industry's capacity to pay catastrophe losses is higher in 2020 than it was in 1997. Insurers could pay 98% of a $200 billion loss in 2020, compared to 81% in 1997.